2020
DOI: 10.1155/2020/8869766
|View full text |Cite
|
Sign up to set email alerts
|

Computational Analysis on Numerical Simulation of Internal Flow Physics for Pump as Turbine in Renewable Small Hydro Energy Generation

Abstract: Energy contributes significantly in almost all aspects of human life as well as economic activities and plays a crucial role in the infrastructural development of a county to alleviate poverty. Generating energy from a renewable source such as small hydropower through the application of pump operating as a turbine mode called Pump as Turbine is one of the best alternatives to provide clean and inexpensive energy. Using Pump as Turbine helps in generating reasonably priced hydroelectric power for communities in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…Cavitation is an important source of instabilities, so it was included in the same query as instabilities. In this group, the following topics are addressed: geometry, efficiency, cavitation [4,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], flow structures [8,[22][23][24][25], pressure fluctuations [16,21,26,27], vortex rope [27], energy losses when switching from pump to turbine mode [28], and application of entropy production theory for energy losses [29]. None of them addresses the measurement of instabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Cavitation is an important source of instabilities, so it was included in the same query as instabilities. In this group, the following topics are addressed: geometry, efficiency, cavitation [4,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], flow structures [8,[22][23][24][25], pressure fluctuations [16,21,26,27], vortex rope [27], energy losses when switching from pump to turbine mode [28], and application of entropy production theory for energy losses [29]. None of them addresses the measurement of instabilities.…”
Section: Introductionmentioning
confidence: 99%
“…With increasing flow rate, the hydrodynamic force on the impeller and pressure fluctuations on the volute first decrease and then increase, reaching a minimum value near the design flow rate. Du et al investigated the internal flow behavior of a centrifugal pump operating as a turbine at different speeds and flow rates and analyzed the vortex behavior, turbulent kinetic energy, pressure, and velocity distribution [20]. The results showed that vortex and turbulent kinetic energy affected the internal flow at PAT, with flow instability and local flow structure at higher speeds and flow rates.…”
Section: Introductionmentioning
confidence: 99%